The Effect Of Performance Evaluation On Employee Performance At The Sidikalang District Office, Dairi Regency - Anny Fonisa Nasution; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
The purpose of this study was to determine and analyze the effect of Performance Evaluation on Employee Performance at the Sidikalang District Office in Dairi Regency. This research was conducted using a quantitative associative causal approach. The sample consisted of all civil servant employees, totaling 49 individuals, selected through purposive sampling. The results showed that Performance Evaluation had a positive and significant effect on Employee Performance. This was indicated by the t-value of 43.221, which was greater than the t-table value of 2.01174, with a significance level of 0.000, which is less than 0.05. The regression coefficient indicated that for every 1-unit increase in Performance Evaluation, Employee Performance would increase by 0.882 units, assuming other variables remained constant. Furthermore, the determination test results showed an Adjusted R Square value of 0.920 or 92.00%, indicating that Performance Evaluation had a very high impact on Employee Performance, while the remaining 8.00% was influenced by other factors not examined in this study. Therefore, Performance Evaluation had a positive and significant effect on Employee Performance at the Sidikalang District Office in Dairi Regency. This finding identifies that improvements in Performance Evaluation can contribute to enhancing Employee Performance.